2015
DOI: 10.1002/jpln.201500001
|View full text |Cite
|
Sign up to set email alerts
|

Forms and solubility of plant nutrient elements in tropical plant waste biochars

Abstract: Thailand is an agriculture-based country which produces large amounts of agricultural waste. Making biochar from this waste can reduce pollution, decrease costs of production, and increase C sequestration. The agronomic benefits of biochar are partly derived from the available plant nutrients in biochar. This study investigated the fertilizer value of biochars manufactured by slow pyrolysis. Pyrolysis temperature and feedstock type affect nutrient concentrations and nutrient element speciation in biochar. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 13 publications
3
35
0
3
Order By: Relevance
“…XRD analysis indicates the crystalline salts (minerals) of biochars and MOF‐5 (Figure ). Two narrow, sharp peaks in MOF‐5 around 12° and 17° were attributed to zinc hydroxide (Zn(OH) 2 ) .…”
Section: Resultsmentioning
confidence: 99%
“…XRD analysis indicates the crystalline salts (minerals) of biochars and MOF‐5 (Figure ). Two narrow, sharp peaks in MOF‐5 around 12° and 17° were attributed to zinc hydroxide (Zn(OH) 2 ) .…”
Section: Resultsmentioning
confidence: 99%
“…Mangosteen shell, pineapple peel, and eucalyptus wood wastes were chosen for this research as they exist in large volumes in many tropical countries [2]. They were dried to 20-30% moisture before the carbonization procedure.…”
Section: Preparation Of Biocharsmentioning
confidence: 99%
“…Biochar may contain substantial amounts of plant nutrient elements, and at normal rates of application of biochar to crops, it may act as a multi-element fertilizer [1,2]. The solubility in extractants of the nutrient compounds (minerals) within biochar and dissolution of these minerals in soils is commonly low due to the intrinsic properties of the minerals and their protected positions within the microporous fabric of biochar [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…It might be assumed that Mg, NH 4 -N, and PO 4 -P in the biochar and pig manure compost could be synthesized to struvite [Mg (NH 4 ) 2 PO 4 •6H 2 O] as slow-release fertilizer during processing time of biochar pellet. Prakongkep et al (2015) reported that the soluble compounds of total Mg and total P contained 1% to 21% and 1% to 33%, respectively, in biochar [33].…”
Section: Patterns Of Accumulated Nh 4 -N Releasing Amount With Differmentioning
confidence: 99%